Dukungan Sosial Teman Sebaya untuk Meningkatkan Kepercayaan Diri Remaja di Panti Asuhan Amal Wanita An-Nur Depok - Daffa Pasya Islami; Muhammad Sahrul (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study investigates the role of peer social support in enhancing self-confidence among adolescents at the Amal Wanita An-Nur Orphanage in Depok, Indonesia. Adolescents living in orphanages often experience psychological challenges, including low self-confidence and limited social interaction, which can affect their personal growth and future orientation. The objective of this research is to explore how peer social support contributes to strengthening self-confidence and to identify the forms, driving factors, and obstacles of such support. A qualitative descriptive method was applied through observation, interviews, and documentation, involving seven informants consisting of the orphanage head, caregivers, and adolescents. Findings show that three types of support emotional, appraisal, and informational play a dominant role in fostering self-confidence. Emotional support was expressed through empathy and active listening, appraisal support was provided through recognition of achievements and encouragement, while informational support involved advice and constructive feedback. Meanwhile, instrumental and network support were less emphasized due to limited resources. Despite the presence of barriers such as feelings of inferiority, miscommunication, and differences in emotional readiness, peer support proved effective in motivating adolescents, strengthening their resilience, and fostering positive self-perception. The implications suggest the need for structured peer-support programs, facilitated by caregivers and social workers, to maximize adolescents’ potential and prepare them for future challenges. Thus, this study demonstrates that peer social support serves not only as a protective factor but also as a social learning tool that shapes adolescents' interpersonal skills. Targeted programs can increase self-confidence, expand social relationships, and create a more supportive and inclusive nursing home environment.